2022
DOI: 10.1111/jonm.13663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of occupational exposure on job satisfaction and overall happiness among Chinese physicians and nurses: A cross‐sectional study

Abstract: Aims This study aims to investigate the impact of occupational exposure on job satisfaction and overall happiness and to identify related factors of job satisfaction and overall happiness among physicians and nurses. Background Occupational exposure against physicians and nurses has become one of the most serious public health issues worldwide. Methods A cross‐sectional study was conducted among physicians and nurses from 14 public tertiary hospitals using purposive sampling. Propensity score matching was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…It is consistent with findings from previous studies (Udod et al, 2017). As reported by other studies (Shi et al, 2022), new nurse managers have experienced excessive workloads and inadequate support, which was also the major cause of their loss.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is consistent with findings from previous studies (Udod et al, 2017). As reported by other studies (Shi et al, 2022), new nurse managers have experienced excessive workloads and inadequate support, which was also the major cause of their loss.…”
Section: Discussionsupporting
confidence: 92%
“…It is consistent with findings from previous studies (Udod et al, 2017 ). As reported by other studies (Shi et al, 2022 ), new nurse managers have experienced excessive workloads and inadequate support, which was also the major cause of their loss. Nevertheless, the female new nurse managers were likely more exhausted due to coping with the pandemic prevention and control work of COVID‐19 for such a long time in this study.…”
Section: Discussionmentioning
confidence: 67%
“…decrease in professional happiness of nurses(Chesaket al, 2019;De Souza et al, 2010;Shi et al, 2022). It can also affect the way nurses work and lead to patient safety issues, such as medical errors(Shi et al, 2022) Studies have shown that positive emotions usually make individuals happy, while facing negative stimuli will produce stress(Piotrkowska et al, 2019), happy people are more satis ed with their jobs than unhappy people(Mignonac et al, 2004). Studies have shown that nurses' happiness positively affects patient care, life satisfaction, job satisfaction, productivity and work e ciency(Abdollahi A et al, 2014).…”
mentioning
confidence: 99%